Penerapan Customer Relationship Management (CRM) pada UMKM Mie Pangsit Ayam Bangka Mr.Ong Batam - Wijaya, Calvin; Dyfan; Noviani, Metta; Raymond; Yendiarti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research was conducted with the aim of being able to analyze the implementation of Customer Relationship Management which is focused on MSMEs in Batam City, namely Mie Pangsit Ayam Bangka Mr. Ong. As well as being able to see any inhibiting factors or the application of the implementation of Customer Relationship Management at MSME Bangka Chicken Dumpling Noodles. Ong who is in Batam City. The method used is descriptive quantitative method, this method is in the form of producing data that is statistical in nature and data collection is carried out by means of interviews, observation and documentation of Bangka Chicken Noodle Mie MSME actors. Ong in Batam City and consumers from UMKM Mie Pangsit Ayam Bangka Pak Ong who are considered to be able to provide accurate information about the product and the application of the CRM itself. The results of this study where the characteristics are to see the implementation of Customer Relationship Management (CRM) in MSMEs in Batam City which can show that MSME actors have been able to implement and run the CRM, although it is still not optimal in its application. With this research, the researchers were able to provide insight and input to MSME actors. Ong about the importance and benefits that will be obtained in implementing Customer Relationship Management (CRM) for businesses that are being pioneered. Keywords: Implementation, Customer Relationship Management, MSMEs